Legal Protection of Husband as A Victim of Domestic Violence - Agus Susanto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In this study, the victims of domestic violence were generally women, and the perpetrators were men. So that so far the laws that have been formed provide more legal protection for wives and the community considers that violence perpetrated by wives against their husbands is a natural thing, because it is part of the dynamics of married life that usually occurs. Domestic violence against men is related to domestic violence experienced by men or boys in intimate relationships such as marriage, living together, or within the family. Domestic violence is a social fact. because it can occur in the household regardless of culture, religion, ethnicity, and age of the perpetrator and the victim. The law on the elimination of domestic violence provides guarantees of protection. Where this form of protection may take the form; temporary protection and protection orders.